GLOBAL HIGH-TECH MARKET: ACTIVITIES OF TRANSNATIONAL CORPORATIONS AND DIGITALIZATION - Карпик, Ярослав М.; Імнадзе, Іраклій Н. (Journal of Strategic Economic Research, 2024)
The activities of transnational corporations (TNCs) in the field of high technologies significantly affect the global high-tech market. Digitization plays a key role in ensuring the competitiveness of TNCs and contributes to their development. That is why the topic of the research is timely and relevant. The purpose of the presented work is to determine the peculiarities and regularities of the activities of transnational corporations under the influence of digitalization processes. The main methods used in the work are the following methods: the method of analysis and synthesis to determine the main patterns of development of transnational corporations in modern conditions of digitalization, the methods of deduction and induction to determine the main directions of development of the global high-tech market and the activities of transnational corporations on it, the method of comparison for determination of the main features of the digitization toolkit, a graphic method for visual display of the presented research results. As a result of the presented work, it is possible to determine the following components that have an impact on the development of TNCs in the conditions of digitalization: the use of digital technologies for the development of e-commerce and optimization of the supply chain; implementation of systems that automate and optimize business process management; financing large research programs to create new products and technologies; creating and maintaining laboratories for testing new ideas and developments; using cloud platforms to provide access to data and resources in real time; use of modern digital security tools to protect confidential information; creation and implementation of products that are able to interact with each other and with users via the Internet; analysis of large volumes of data coming from connected devices to obtain valuable information; use of artificial intelligence to automate task solving and increase efficiency; application of data analytics to obtain insights and make strategic decisions; application of blockchain technology to ensure security and transparency in financial transactions; using automated smart contracts to manage transactions and interact with counterparties. That is why it is necessary to introduce digital technologies in production to automate and optimize processes.